PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) DAN DIRECT INSTRUCTION TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI IPA SMA NEGERI 1 KOTABARU TAHUN PELAJARAN 2018/2019 - Faisal Batennie (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2021)
This study is (1) To determine the mathematics learning outcomes of class XI IPA students of SMA Negeri 1 Kotabaru in mathematics learning using the think talk write cooperative learning model. (2) To find out the mathematics learning outcomes of XI IPA students of SMA Negeri 1 Kotabaru in mathematics learning using direct instruction learning model. (3) To find out whether there is a significant difference in mathematics learning outcomes after using the cooperative learning model Think talk write (TTW) type and direct instruction learning model for XI IPA class students of SMA Negeri 1 Kotabaru. (4) To determine the response of class XI IPA students of SMA Negeri 1 Kotabaru when the think talk write (TTW) type of cooperative learning model is applied and the direct instruction learning model. This study uses an experimental method with a quantitative descriptive approach. The subjects of this study were students of class XI IPA SMA Negeri 1 Kotabaru. Class XI IPA 1 as the experimental class and class XI IPA 3 as the control class. The material taught is integral. Keywords: comparison, cooperative learning model think talk write, direct instruction, and learning outcomes.